Long-term review of the lumbar spine in javelin throwers - Schmitt, H.; Brocai, D. R.; Carstens, C. (The Journal of Bone & Joint Surgery (British Volume), 2001)
We studied 21 former top-class competitive javelin throwers to investigate radiological and clinical symptoms in the lumbar spine many years after the end of their athletic careers. The athletes underwent clinical and radiological examinations at an average of 20 years after retiring from athletics. The Hannover questionnaire was used to evaluate functional restrictions in daily living. Degenerative changes in the lumbar spine were more marked towards the caudal aspect of the spine. Ten athletes also had spondylolisthesis, but with little progression (< 15%) throughout the observation period. Athletes both with and without radiologically demonstrated spondylolisthesis, complained of no more back problems than the normal population (93% for athletes v 86% for controls). Slight progression followed their retirement from athletics.